Student Perspectives On Coffee Shop Marketing Management On Campus In The Era Of Digital Business - Najihatul Faridy; Imam Gunanjar (Jurnal Investasi Islam, 2026)
The rapid development of the digital era has significantly influenced marketing practices, including those adopted by coffee shops operating on university campuses. However, many campus coffee shops still face challenges in adapting to digital-based marketing management due to limited facilities, infrastructure, and worker competencies in utilizing digital technologies. Therefore, this study aims to analyze students’ perspectives on the marketing management of campus coffee shops in relation to the implementation of digital business practices. This study employed a descriptive research approach using a survey method. Data were collected through questionnaires using a Likert scale to measure students’ perceptions of coffee shop marketing management and the use of digital technology. The research participants consisted of 50 students who purchased coffee at the Semerbak Canteen, Samudra University, selected through purposive sampling. Data collection was conducted from December 14 to December 28, 2025.The findings indicate that the implementation of digital business in campus coffee shop marketing provides several benefits for students. First, digital ordering systems and online menu access through smartphones improve convenience and efficiency in the purchasing process. Second, the availability of facilities such as Wi-Fi and a comfortable environment supports students’ academic activities, including studying and completing assignments. Third, the integration of digital marketing strategies contributes positively to the image and attractiveness of campus coffee shops among students.In conclusion, the adoption of digital business practices in campus coffee shop marketing management can enhance service accessibility, improve customer experience, and strengthen the competitiveness of campus-based coffee shops in the digital era.